Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcvm.2021.739212
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban Suppresses Atherosclerosis by Inhibiting FXa-Induced Macrophage M1 Polarization-Mediated Phenotypic Conversion of Vascular Smooth Muscle Cells

Abstract: Background: Factor Xa (FXa) is a mediator initiating and accelerating atherosclerosis (AS). Both macrophage and vascular smooth muscle cells (VSMCs) participate in AS progression. This study was aimed to investigate the mechanisms underlying the effects of the FXa inhibitor rivaroxaban on AS.Methods: Rivaroxaban was administered to AS mice. Primary macrophages were exposed to FXa, treated with rivaroxaban, and transfected with siRNA silencing protease-activated receptor 2 (PAR2), hypoxia-inducible factor 1α (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Contact and noncontact coculture models were adopted from our previous investigation [ 5 ] which was demonstrated in Figure 1(a) . According to previous descriptions, macrophages were cocultured with VSMCs in Millicell-24 Cell Culture Insert Plate system with polyethylene terephthalate membranes (Millipore) [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact and noncontact coculture models were adopted from our previous investigation [ 5 ] which was demonstrated in Figure 1(a) . According to previous descriptions, macrophages were cocultured with VSMCs in Millicell-24 Cell Culture Insert Plate system with polyethylene terephthalate membranes (Millipore) [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…When challenged by harmful stimuli, VSMCs lose contractile properties and convert into synthetic phenotype which is critical in formation and progression of atherosclerotic plaques [ 2 ]. Ours and others' previous studies suggested that delta-like ligand 4- (Dll4-) activated Notch signaling pathway was indispensable in VSMC contractile-synthetic phenotypic conversion [ 3 5 ]. It was reported that Dll4 blockage effectively attenuated several metabolic disorders including atherosclerosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study found that rivaroxaban reduced that proinflammatory effects of FXa on human umbilical vein endothelial cells [31]. It was also reported that FXa induces phenotypic conversion of vascular smooth muscle cells into macrophages [32]. A recent study demonstrated that rivaroxaban reduces atherosclerosis by preventing FXa-PAR2-dependent autophagy suppression [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to macrophage infiltration ( 24 , 25 ), phenotypic transformation of VSMCs is a key mechanism in aneurysms ( 26 ) and atherosclerosis ( 27 ), so as the endothelial dysfunction ( 28 , 29 ). It is noteworthy that macrophages have regulatory effects on vascular smooth muscle cells ( 30 ), endothelial cells and macrophages themselves ( 31 ). Meanwhile, macrophage infiltration was a pathological feature of the cardiovascular system after SARS-CoV-2 infection ( 32 ).…”
Section: Discussionmentioning
confidence: 99%